2021
DOI: 10.3389/fonc.2021.685893
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-Specific Expression of HEXA and HEXB Leads to Poor Prognosis in Glioblastoma Patients

Abstract: Glioblastoma multiforme (GBM) is one of the deadliest cancers in brain. There have been few treatment advances for GBM despite increasing scientific understanding of this disease. β-hexosaminidase (Hex) is an important enzyme system in human body, encoded by two genes, HEXA and HEXB, are closely related to central nervous system (CNS) diseases such as Sandhoff disease (SD) and Tay-Sachs disease (TSD). However, the expression pattern and function of HEXA and HEXB in GBM remains unclear. Here, we found that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In humans, HEXB is an important lysosomal enzyme involved in the degradation of various cellular substrates (Jia et al., 2021 ). Accumulating studies have shown that HEXB is associated with various central nervous system diseases (Kostallari et al., 2021 ; Sierksma et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, HEXB is an important lysosomal enzyme involved in the degradation of various cellular substrates (Jia et al., 2021 ). Accumulating studies have shown that HEXB is associated with various central nervous system diseases (Kostallari et al., 2021 ; Sierksma et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HEXB is highly expressed in several cancers, such as laryngeal cancer (Olszewska et al., 2009 ) and glioblastoma multiforme (Jia et al., 2021 ). However, the precise mechanisms underlying the high level of HEXB in cancer cells still require further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it was not detected in CNS-associated macrophages according to Masuda et al (2020) ; however, it has been identified in non-CNS cells, such as Ly6C + monocytes obtained from the bone marrow ( Hickman et al, 2013 ; Monaghan et al, 2019 ; Masuda et al, 2020 ; Shah et al, 2022 ). HEXB may also play a role in pathology, with elevated gene expression of HEXB associated with poor prognosis in human glioblastoma ( Jia et al, 2021 ). Although HEXB immunostaining has been utilized in combination with TMEM119 to directly identify microglia ( Jia et al, 2021 ), Hexb -based gene reporter and fate mapping tools, have also recently provided important insights into the behavior and functions of microglia in vivo ( Masuda et al, 2020 ).…”
Section: Antibody-mediated Identification Of Microglial Markersmentioning
confidence: 99%
“…HEXB may also play a role in pathology, with elevated gene expression of HEXB associated with poor prognosis in human glioblastoma ( Jia et al, 2021 ). Although HEXB immunostaining has been utilized in combination with TMEM119 to directly identify microglia ( Jia et al, 2021 ), Hexb -based gene reporter and fate mapping tools, have also recently provided important insights into the behavior and functions of microglia in vivo ( Masuda et al, 2020 ). Additionally, the promoter region of Hexb has recently been characterized, enabling the study of Hexb as a potential target for microglia-targeted gene therapies in humans ( Shah et al, 2022 ).…”
Section: Antibody-mediated Identification Of Microglial Markersmentioning
confidence: 99%
“…More critically, another advanced single-cell technology, namely cytometry by time of flight (CyTOF), showed that TMEM119 and P2RY12 were expressed on microglia isolated from postmortem human brains and were absent from myeloid cells in human blood and cerebrospinal fluid (Bottcher et al, 2019 ). Accordingly, in humans, it is tempting to regard TMEM119 and P2RY12 as the most reliable markers that can identify “genuine microglia” in humans, while Siglech (sialic-acid-binding immunoglobulin-like lectin-h) (Bedard et al, 2007 ; Konishi et al, 2017 ) and Hexb (beta-hexosaminidase subunit beta) (Masuda et al, 2020 ; Jia et al, 2021 ) are also considered as microglia-enriched genes ( Table 1 ).…”
Section: Specific Markers Segregating Myeloid Cells In the Brainmentioning
confidence: 99%